Effect of illness perception improvement on risk factors of coronary artery disease - Zolfaghari Lake Z; Roohani M; Shakibazadeh E; Kamali K (Zanjan University of Medical Sciences and Health Services, 2017)
Background: Illness perception can affect health-related behaviors and disease outcomes. Objectives: To determine the effect of an educational intervention of improving illness perception on some modifiable risk factors of coronary artery disease. Methods: In this clinical trial, 100 patients undergoing coronary angiography that met the inclusion criteria were divided randomly into two intervention and control groups. In the intervention group, three educational sessions were conducted individually, while usual care was conducted for the control group. Measurements on fasting blood glucose, cholesterol, triglyceride, blood pressure, body mass index, and smoking status were gathered at baseline, immediately and six months after the intervention in both groups. Data were analyzed using the SPSS. Results: The mean of systolic blood pressure (p<0.005), fasting triglycerides (p<0.005), and fasting blood glucose (p<0.005) were significantly different before and after the intervention between the two groups. Conclusion: Improvement illness perception through educational intervention can affect risk factors of coronary artery disease.